Topography of stomach ulcer - Suiffet, Walter; Sojo, Enrique; Iraola, María L (Cirugía del Uruguay, 1977)
Topography of gastric ulcer in connection with various gastric sectors -different areas of gastric mucosa and muscular structure of stomach- is analyzed. The analysis of 115 personal cases showed that gastric ulcers are located in 80-90 % of cases in the minor curve, in its dist<?l 2/3. Its greater incidence is in the sinus angularis ( 80%) followed by prepyloric area (15.6 % of cases); the most infrequent being the higher area ( 4. 4 % ) . Coexistance with duodenal ulcer was 14 %- Gastric ulcers are generally found in pyloric glands and there were no cases of location in any other type of mucosa. In general, the lesion is either in, or very near, the border area. At the same leve! and on lateral, walls, there is íundic mucosa reaching nearer the pylorus that the pyloric mucosa. These concepts apply regardless oí the topography oí the gastric ulcer.